2018
DOI: 10.1186/s12875-018-0762-1
|View full text |Cite
|
Sign up to set email alerts
|

Influences of peer facilitation in general practice – a qualitative study

Abstract: BackgroundPractice facilitation is increasingly used to support guideline implementation and practice development in primary care and there is a need to explore how this implementation approach works in real-life settings.We focus on a facilitation intervention from the perspective of the visited practices to gain a more detailed understanding of how peer facilitation influenced practices and how they valued the facilitation.MethodsThe facilitation intervention was conducted in general practice in the Capital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
45
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(48 citation statements)
references
References 27 publications
0
45
0
Order By: Relevance
“…A unique and novel aspect to our proposal is that for the first time these components have been combined into a useful primary care ‘tool box’ for the treatment of LBP. The components included in our implementation strategy are therefore multifaceted and described on a general level and we would highlight that some of the individual components may need to be adapted following an assessment of the specific national context and change opportunities [28].…”
Section: Introductionmentioning
confidence: 99%
“…A unique and novel aspect to our proposal is that for the first time these components have been combined into a useful primary care ‘tool box’ for the treatment of LBP. The components included in our implementation strategy are therefore multifaceted and described on a general level and we would highlight that some of the individual components may need to be adapted following an assessment of the specific national context and change opportunities [28].…”
Section: Introductionmentioning
confidence: 99%
“…The impact of peers for making changes in general practice is also well known in the literature; one example is the positive impact on practice facilitation [ 7 , 8 ]. The importance of peers is also acknowledged in the accreditation survey as one of the surveyors is a GP [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study also found that some clinics supplemented the regional support with informal support from experts and colleagues [ 6 ]. We know from other quality interventions that practice facilitation and peer discussion can be useful [ 7 , 8 ], but it remains unknown whether these tools are used and perceived as useful in the accreditation process.…”
Section: Introductionmentioning
confidence: 99%
“…Coaching has less frequently been used to facilitate practice change, as practice facilitators are typically used in studies of clinical transformation where they assist in adopting quality improvement and change management processes to implement new approaches to care. [7][8][9] However, they seldom have experience with the training of health professionals.…”
Section: Introductionmentioning
confidence: 99%